Diet quality as a predictor of cardiometabolic disease-free life expectancy: the Whitehall II cohort study - Lagström H; Stenholm S; Akbaraly T; Pentti J; Vahtera J; Kivimäki M; Head J (OXFORD UNIV PRESS, 2022)
Background: Poor diet quality has been linked to increased risk of many chronic diseases and premature mortality. Less research has considered dietary habits in relation to disease-free life expectancy.Objectives: Our objective was to investigate the association of diet quality with cardiometabolic disease-free life expectancy between ages 50 and 85 y.Methods: Diet quality of 8041 participants of the Whitehall II cohort study was assessed with the Alternative Healthy Eating Index 2010 (AHEI-2010) in 1991-1994, 1997-1999, and 2002-2004. The measurement of diet quality closest to age 50 for each participant was used. We utilized repeat measures of cardiometabolic disease (coronary heart disease, stroke, and type 2 diabetes) from the first observation when participants were aged >= 50 y. Multistate life table models with covariates age, gender, occupational position, smoking, physical activity, and alcohol consumption were used to estimate total and sex-specific cardiometabolic disease-free life expectancy from age 50 to 85 y for each AHEI-2010 quintile, where the lowest quintile represents unhealthiest dietary habits and the highest quintile the healthiest habits.Results: The number of cardiometabolic disease-free life-years after age 50 was 23.9 y (95% CI: 23.0, 24.9 y) for participants with the healthiest diet, that is, a higher score on the AHEI-2010, and 21.4 y (95% CI: 20.6, 22.3 y) for participants with the unhealthiest diet. The association between diet quality and cardiometabolic disease-free life expectancy followed a dose-response pattern and was observed in subgroups of participants of different occupational position, BMI, physical activity level, and smoking habit, as well as when participants without cardiometabolic disease at baseline were excluded from analyses.Conclusions: Healthier dietary habits are associated with cardiometabolic disease-free life expectancy between ages 50 and 85.